Silica sol and silica-based aerogel composite material

By using deionized water and surfactants in the preparation of silicon-based aerogel composites, combined with atmospheric drying method and hexamethylenetetramine catalysis, the environmental and safety problems brought about by the use of organic solvents are solved, and the efficient preparation of low-density and low-thermal conductivity of silicon-based aerogel composites is achieved.

CN119873835APending Publication Date: 2025-04-25AVIC BEIJING AERONAUTICAL MFG TECH RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411865214.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing silicon-based aerogel composite preparation process is widely used, which has the risks of flammable and explosiveness and environmental pollution. The drying process consumes a lot of energy and is not suitable for large-sized preparation.

Method used

Deionized water is used as solvent and silicon-based aerogel composite material is prepared by atmospheric drying method, cetyl trimethylammonium bromide is used as surfactant to regulate the pore structure, and hexamethylenetetramine is used as base catalyst to control the crosslinked polymerization structure.

Benefits of technology

The preparation of silicon-based aerogel composite materials without organic solvents is realized, reducing the risks of environmental pollution and flammability and explosion, and the process is fast and efficient, suitable for large-size preparation, and the product has low density and low thermal conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873835A_ABST
    Figure CN119873835A_ABST
Patent Text Reader

Abstract

The invention relates to silica sol and a silica-based aerogel composite material. A preparation method of the silica sol comprises the steps of preparation of the silica sol, preparation of a ceramic fiber preform, an RTM (Resin Transfer Molding) impregnation process, a heating curing process and a normal-pressure drying process. Deionized water is adopted as a solvent, the water solvent is directly removed in a normal-pressure drying mode, and the whole preparation process has the advantages of being rapid, efficient and environmentally friendly. The alkali catalyst hexamethylenetetramine is adopted, and the characteristic that the alkali catalyst hexamethylenetetramine is decomposed to release ammonia gas under the heating condition is utilized, so that the cross-linking polymerization structure of a silica-based gel network is uniform and controllable. The silicon-based aerogel composite material prepared by the invention has the performance characteristics of low density and low heat conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of fiber-reinforced aerogel composite materials, in particular to a method for preparing a silicon-based aerogel composite material by a normal pressure drying method, and in particular to a silica sol and a silicon-based aerogel composite material. Background Art

[0002] Insulating ceramic-based composite materials have been widely used in aerospace, construction, new energy and other fields. In order to reduce costs and improve the industrial batch production capacity of silicon-based aerogel composite materials, the atmospheric pressure drying preparation technology of silicon-based aerogel and its composite materials has become a research hotspot, and rich research results have been achieved. However, there are still the following problems that need to be further improved: organic solvents with flammable and explosive properties are still widely used in the entire process, including the use of organic solvents such as ethanol in the sol stage, low surface tension organic solvents such as n-hexane in the solvent replacement stage, and organic solvents directly volatilize into the atmosphere in the gel drying stage. Therefore, the disadvantage of the entire process is that on the one hand, it has potential flammable and explosive risk characteristics, and on the other hand, it also causes certain pollution to the environment.

[0003] The wet gel needs to be dried to remove the solvent to obtain aerogel. During the drying process, the original network skeleton structure should be retained as much as possible. By replacing the liquid in the network structure with gas through an appropriate drying process, a porous solid material with high porosity and high specific surface area can be obtained. Common drying methods include supercritical drying, freeze drying, and atmospheric pressure drying. Different drying methods have a great influence on the microstructure.

[0004] Supercritical drying refers to placing the wet gel in a sealed container and increasing the temperature and pressurization to make the solvent inside the gap reach its supercritical point. This requires the sealed container to be treated with high temperature and high pressure, which is energy-consuming and relatively dangerous. Freeze drying usually places the wet gel in a freeze dryer. After pre-freezing and thorough freezing, the solvent is completely condensed, and then the pressure is gradually reduced. The solidified solvent directly sublimates into a gas under low pressure. This process also requires the use of equipment and is not suitable for the preparation of large-sized and special-shaped components.

[0005] Patent CN 115012208 B discloses a high-efficiency atmospheric pressure drying large-scale preparation method for silica aerogel felt, wherein the preparation of methylsilanol solution adopts one or more of methanol, ethanol, isopropanol, and n-butanol, and one or more of n-hexane, n-heptane, and n-pentane with low surface tension characteristics are adopted in the secondary hydrophobic modification process, and the prepared aerogel is granular in morphology, and the whole process inevitably adopts organic solvent as medium; Patent CN 116375042 A discloses a low-cost preparation method of inorganic silicon-based aerogel, in the process of solvent replacement of SiO2 wet gel, the organic solvent of functional silane is used for replacement, wherein the functional silane adopts one of dimethylchlorosilane or trimethylchlorosilane, and the organic solvent is one of ethanol, methanol, or isopropanol.

[0006] Resin Transfer Molding (RTM) is a process in which resin is injected into a closed mold to infiltrate the reinforcing material and solidify it.

[0007] Therefore, it is necessary to provide a method for preparing a silicon-based aerogel composite material based on existing research, which only uses deionized water as a solvent and does not involve any organic solvents in the entire process. At the same time, the preparation process is controllable, the drying process can use normal pressure drying, and the final silicon-based aerogel composite material has the performance characteristics of low density and low thermal conductivity.

[0008] In summary, it is very necessary to provide a solution for preparing silica sol and silica-based aerogel composite materials. Summary of the invention

[0009] 1. Technical issues to be resolved

[0010] The technical problem to be solved by the present invention is to prepare silicon-based aerogel by a normal pressure drying method without using an organic solvent, thereby reducing environmental pollution.

[0011] (II) Technical solution

[0012] In order to solve the above technical problems, the present invention provides a silica sol, wherein the raw materials for preparing the silica sol include small siloxane molecules, hexadecyltrimethylammonium bromide, deionized water, hydrochloric acid, and hexamethylenetetramine;

[0013] Wherein, the mass ratio of the hexadecyl trimethyl ammonium bromide to the siloxane small molecule is (1.20×10 -3 ~2.0×10 -1 ):1;

[0014] The mass ratio of the deionized water to the siloxane small molecule is (1.0-4.0):1;

[0015] The ratio of the mass of hydrogen chloride contained in the hydrochloric acid to the mass of the siloxane small molecules is (2.5×10 -5 ~6.0×10 -3 ):1;

[0016] The mass ratio of the hexamethylenetetramine to the siloxane small molecule is (0.01-0.5):1.

[0017] As a preferred embodiment of the present invention, in the silica sol,

[0018] The mass ratio of the hexadecyltrimethylammonium bromide to the siloxane small molecule is (2.12×10 -3 ~2.0×10 -1 ):1;

[0019] The mass ratio of the deionized water to the siloxane small molecule is (2.9-4.0):1;

[0020] The ratio of the mass of hydrogen chloride contained in the hydrochloric acid to the mass of the siloxane small molecules is (2.5×10 -5 ~3.2×10 -3 ):1;

[0021] The mass ratio of the hexamethylenetetramine to the siloxane small molecule is (0.02-0.5):1.

[0022] As a preferred embodiment of the present invention, the siloxane small molecule is selected from one or more of tetramethyl orthosilicate, tetraethyl orthosilicate, methyltriethoxysilane, methyltrimethoxysilane, ethyltriethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, phenyltriethoxysilane, phenyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, octadecyltrimethoxysilane, and octadecyltriethoxysilane.

[0023] The present invention also provides a method for preparing silica sol, comprising the steps of:

[0024] Mix small siloxane molecules, deionized water and hydrochloric acid, stir at room temperature for 2 to 5 hours to hydrolyze siloxane; introduce hexadecyltrimethylammonium bromide, stir for 10 to 40 minutes, and finally introduce hexamethylenetetramine, stir at room temperature for 0.5 to 1.0 hours to form a homogeneous solution to obtain the silica sol for standby use; the stirring rate during the whole process is controlled at 50 to 300 r / min.

[0025] The present invention also provides a silicon-based aerogel composite material, which is prepared using the silica sol of the present invention, comprising the steps of:

[0026] S1. Using the RTM process, first lay a ceramic fiber preform in the mold cavity of the RTM metal mold and evacuate it;

[0027] S2. Maintaining the vacuum degree of the RTM metal mold at -0.090 MPa to -0.095 MPa, maintaining the negative pressure for 0.5 h to 1.5 h, introducing silica sol into the mold cavity of the RTM metal mold, allowing the silica sol to impregnate the ceramic fiber preform, and then pressurizing to 0.2 MPa to 0.4 MPa, maintaining the pressure for 1 to 4 h, and completing the impregnation process;

[0028] S3. The RTM metal mold impregnated with S2 is heated and cured, and then demolded to obtain a flat member;

[0029] S4. The flat plate component is heated to remove water to obtain a silicon-based aerogel composite material.

[0030] As a preferred embodiment of the present invention, the fiber used in the ceramic fiber preform is selected from one of quartz fiber, mullite fiber, alumina fiber and zirconia fiber.

[0031] As a preferred embodiment of the present invention, the apparent density of the ceramic fiber preform is 0.05 g / cm 3 ~0.15g / cm 3 .

[0032] As a preferred embodiment of the present invention, the heating and curing process in step S3 includes: curing by heating in an oven, the heating temperature is 70° C. to 100° C., and the heating time is 10 h to 40 h.

[0033] As a preferred embodiment of the present invention, the heating and dehydration process in step S4 includes: heating at 60°C to 80°C for 8h to 10h, and then heating to 100°C to 120°C for 3h to 6h.

[0034] (III) Beneficial effects

[0035] The above technical solution of the present invention has the following advantages:

[0036] 1. The present invention introduces the surfactant hexadecyltrimethylammonium bromide into the silica sol. The surfactant molecular structure is amphiphilic, that is, it has both a hydrophilic group and a hydrophobic group. After the surfactant molecules are dissolved in water, the hydrophilic group will face the water, while the hydrophobic group will face the air. This directional arrangement significantly reduces the surface tension of water, so that it can replace the organic solvent as a solvent in the preparation process.

[0037] 2. The surfactant hexadecyltrimethylammonium bromide used in the present invention also achieves the regulation of pore structure. In the polymerization reaction stage of siloxane, the surfactant plays a role of soft template. A certain concentration of surfactant can be aggregated into spherical or rod-shaped micelles in aqueous solution, and the polymerized particles grow along the periphery or inside of the micelle, so that the surfactant has a certain template effect; and ionic surfactants usually adsorb H + Or OH-, thereby changing the pH value of the solution, and therefore has a certain catalytic effect on the polymerization process.

[0038]

[0039] Note: R represents -OH, -CH3, -CH2CH3, or

[0040] 3. The present invention uses deionized water as a solvent and directly removes the water solvent by drying at normal pressure. This is different from the traditional methods of removing organic solvents, such as supercritical drying and freeze drying, which are energy-intensive and dangerous and are not suitable for preparing large-sized and special-shaped components. The entire preparation process of the present invention is fast, efficient, and environmentally friendly.

[0041] 4. The present invention uses hexamethylenetetramine as a base catalyst, and utilizes its characteristic of decomposing and releasing ammonia under heating conditions to make the cross-linked polymerization structure of the silicon-based gel network uniform and controllable.

[0042] 5. The silicon-based aerogel composite material developed by the present invention has the performance characteristics of low density and low thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a graph showing the change in thermal conductivity of the silicon-based aerogel composite material provided in Example 2;

[0044] Figure 2 This is a macroscopic photograph of the silicon-based aerogel composite material provided in Example 2;

[0045] Figure 3 This is a microscopic morphology of the silicon-based aerogel composite material provided in Example 2. DETAILED DESCRIPTION

[0046] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0047] Example 1

[0048] This embodiment provides a silica sol, which is made of siloxane small molecules, cetyltrimethylammonium bromide (CTAB), deionized water, hydrochloric acid, and hexamethylenetetramine (HMTA).

[0049] The siloxane small molecule is a mixture of tetraethyl orthosilicate and phenyltriethoxysilane, and the mass ratio of tetraethyl orthosilicate to phenyltriethoxysilane is 3:7;

[0050] The hydrochloric acid is concentrated hydrochloric acid with a concentration of 37%.

[0051] The mass ratio of CTAB to siloxane small molecules is 1.8×10 -2 :1.

[0052] The mass ratio of deionized water to siloxane small molecules is 2.9:1.

[0053] The mass ratio of hydrogen chloride contained in concentrated hydrochloric acid to the mass ratio of siloxane small molecules is 2.5×10 -5 :1.

[0054] The mass ratio of HMTA to siloxane small molecules is 0.21:1.

[0055] The preparation method of the silica sol provided in this embodiment includes: tetraethyl orthosilicate, phenyltriethoxysilane, deionized water and hydrochloric acid are mixed, and stirred at room temperature for 3 hours. During this process, the siloxane undergoes a hydrolysis reaction, and then hexadecyltrimethylammonium bromide is introduced, and stirring is continued for 30 minutes. Finally, hexamethylenetetramine is introduced, and stirring is continued at room temperature for 1.0 hour. After a homogeneous solution is formed, a silica sol is obtained and set aside. The stirring rate during the whole process is controlled at 300r / min.

[0056] This embodiment also provides a silicon-based aerogel composite material, which is prepared using the above-mentioned silica sol, and the preparation method includes the following steps:

[0057] (1) Preparation of ceramic fiber preform: According to the inner cavity size of the metal mold, a ceramic fiber preform with a density of 0.1 g / cm 3 The quartz fiber preform is cut to the specified size, and after the mold is installed, it is evacuated to -0.092MPa and a negative pressure test is performed.

[0058] (2) RTM impregnation: Based on the RTM pipeline system built in the first step, the vacuum range is maintained at -0.092 MPa. After maintaining the negative pressure for 1 hour, the prepared silica sol is fully impregnated into the mold cavity with the help of atmospheric pressure to allow the silica sol and the ceramic fiber preform to be fully mixed. The pressure is continued to be increased to 0.2 MPa, maintained for 4 hours, and the inlet and outlet valves are closed.

[0059] (3) Heating and curing: After the impregnation in the above step, the closed metal mold is placed in an oven for heating and curing at a temperature of 80°C for 20 hours. After curing, the mold is cooled and demolded.

[0060] (4) Drying at normal pressure: The demoulded flat plate component is placed in an oven for heating treatment to remove the water solvent. The heating procedure is heating at 70°C for 8 hours and heating at 100°C for 3 hours. Finally, a silicon-based aerogel composite material is obtained.

[0061] Example 2

[0062] This embodiment provides a silica sol, which is made of siloxane small molecules, cetyltrimethylammonium bromide (CTAB), deionized water, hydrochloric acid, and hexamethylenetetramine (HMTA).

[0063] The siloxane small molecule is a mixture of methyltrimethoxysilane and dodecyltrimethoxysilane, and the mass ratio of methyltrimethoxysilane to dodecyltrimethoxysilane is 5:5;

[0064] The hydrochloric acid is concentrated hydrochloric acid with a concentration of 37%.

[0065] The mass ratio of CTAB to siloxane small molecules is 2.12×10 -3 :1.

[0066] The mass ratio of deionized water to siloxane small molecules is 3.9:1.

[0067] The ratio of the mass of hydrogen chloride contained in concentrated hydrochloric acid to the mass of siloxane small molecules is 2.78×10 -4 :1.

[0068] The mass ratio of HMTA to siloxane small molecules is 0.12:1.

[0069] The preparation method of the silica sol provided in this embodiment includes: methyltrimethoxysilane, dodecyltrimethoxysilane, deionized water and hydrochloric acid are mixed, and stirred at room temperature for 3 hours. During this process, the siloxane undergoes a hydrolysis reaction, and then hexadecyltrimethylammonium bromide is introduced, and stirring is continued for 30 minutes. Finally, hexamethylenetetramine is introduced, and stirring is continued at room temperature for 1.0 hour. After a homogeneous solution is formed, a silica sol is obtained and set aside. The stirring rate during the whole process is controlled at 300r / min.

[0070] The present embodiment provides a method for preparing a silicon-based aerogel composite material, which is prepared using the above-mentioned silica sol, and the preparation method comprises the following steps:

[0071] (1) Preparation of ceramic fiber preform: According to the inner cavity size of the metal mold, a ceramic fiber preform with a density of 0.15 g / cm 3 The mullite fiber preform is cut to the specified size. After the mold is installed, it is evacuated to -0.095MPa and a negative pressure test is performed.

[0072] (2) RTM impregnation: Based on the RTM pipeline system built in the first step, the vacuum range is maintained at -0.090 MPa. After maintaining the negative pressure for 1 hour, the prepared silica sol is fully impregnated into the mold cavity with the help of atmospheric pressure to allow the silica sol and the ceramic fiber preform to be fully mixed. The pressure is then increased to 0.3 MPa and maintained for 3 hours, and the inlet and outlet valves are closed.

[0073] (3) Heating and curing: After the impregnation in the above step, the closed metal mold is placed in an oven for heating and curing at a temperature of 95°C for 30 hours. After curing, the mold is cooled and demolded.

[0074] (4) Drying at normal pressure: The demoulded flat plate component is placed in an oven for heating treatment to remove the water solvent. The heating procedure is heating at 80°C for 9 hours and heating at 110°C for 3 hours. Finally, a silicon-based aerogel composite material is obtained.

[0075] Example 3

[0076] This embodiment provides a silica sol, which is made of siloxane small molecules, cetyltrimethylammonium bromide (CTAB), deionized water, hydrochloric acid, and hexamethylenetetramine (HMTA).

[0077] Among them, the siloxane small molecule is vinyltrimethoxysilane;

[0078] The hydrochloric acid is concentrated hydrochloric acid with a concentration of 37%.

[0079] The mass ratio of CTAB to vinyltrimethoxysilane is 1.5×10 -2 .

[0080] The mass ratio of deionized water to vinyltrimethoxysilane is 4.0.

[0081] The ratio of the mass of hydrogen chloride contained in concentrated hydrochloric acid to the mass of vinyltrimethoxysilane is 3.2×10 -3 .

[0082] The mass ratio of HMTA to vinyltrimethoxysilane is 0.02:1.

[0083] The preparation method of silica sol provided in this embodiment includes: vinyltrimethoxysilane, deionized water and hydrochloric acid are mixed, and stirred at room temperature for 3 hours. During this process, siloxane undergoes a hydrolysis reaction, and then hexadecyltrimethylammonium bromide is introduced, and stirring is continued for 30 minutes. Finally, hexamethylenetetramine is introduced, and stirring is continued at room temperature for 1.0 hour. After a homogeneous solution is formed, it is set aside to obtain silica sol. The stirring rate during the whole process is controlled at 300r / min.

[0084] The present embodiment provides a method for preparing a silicon-based aerogel composite material, which is prepared using the above-mentioned silica sol, and the preparation method comprises the following steps:

[0085] (1) Preparation of ceramic fiber preform: According to the inner cavity size of the metal mold, a ceramic fiber preform with a density of 0.12 g / cm 3 The zirconia fiber preform is cut to the specified size, and after the mold is installed, it is evacuated to -0.093MPa and a negative pressure test is performed.

[0086] (2) RTM impregnation: Based on the RTM pipeline system built in the first step, the vacuum range is maintained at -0.091 MPa. After maintaining the negative pressure for 1 hour, the prepared silica sol is fully impregnated into the mold cavity with the help of atmospheric pressure to allow the silica sol and the ceramic fiber preform to be fully mixed. The pressure is continued to be increased to 0.2 MPa, maintained for 4 hours, and the inlet and outlet valves are closed.

[0087] (3) Heating and curing: After the impregnation in the above step, the closed metal mold is placed in an oven for heating and curing at a temperature of 85°C for 35 hours. After curing, the mold is cooled and demolded.

[0088] (4) Drying at normal pressure: The demoulded flat plate component is placed in an oven for heating treatment to remove the water solvent. The heating procedure is heating at 80°C for 10 hours and heating at 115°C for 3 hours. Finally, a silicon-based aerogel composite material is obtained.

[0089] The performance of the silicon-based aerogel composite materials provided in the above examples was tested, and the thermal conductivity change curve of the silicon-based aerogel composite materials provided in Example 2 is shown in FIG. Figure 1 As shown, macroscopic photos are shown in Figure 2 , microscopic morphology Figure 3 .

[0090] Figure 1 The thermal conductivity of silicon-based aerogel composite materials changes with temperature. The test method is the thermal conductivity test method of refractory materials (water flow plate method). As the temperature rises from 200°C to 1000°C, the thermal conductivity gradually increases, but it is still less than 0.10 W·m -1 ·K -1 , indicating that the composite material exhibits obvious low thermal conductivity.

[0091] Figure 2 This is a macroscopic optical photograph of a silicon-based aerogel composite material. The sample is white in color, 110×110 mm in size, and has an apparent density of 0.25 g / cm 3 .

[0092] Figure 3The figure shows the microscopic morphology of the silicon-based aerogel composite material. It can be seen from the figure that the fibers and the aerogel matrix are interpenetrating with each other, showing the distribution characteristics of micro-nano pore sizes. Among them, the porous silicon-based aerogel shows typical particle stacking morphology characteristics, filling the pores between fibers and adhering to the fiber surface at the same time. The interface between the fiber and the matrix is ​​tightly bonded.

[0093] It should be clear that the various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. For the embodiments of the method, the relevant parts can refer to the partial description of the device embodiment (adopted according to the writing situation). The present invention is not limited to the specific steps and structures described above and shown in the figures. In addition, for the sake of simplicity, a detailed description of known method technologies is omitted here.

[0094] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A silica sol, characterized in that: The raw materials for preparing the silica sol include small siloxane molecules, hexadecyltrimethylammonium bromide, deionized water, hydrochloric acid, and hexamethylenetetramine; Wherein, the mass ratio of the hexadecyl trimethyl ammonium bromide to the siloxane small molecule is (1.20×10 -3 ~2.0×10 -1 ): 1; and / or, The mass ratio of the deionized water to the siloxane small molecules is (1.0-4.0):1; and / or, The ratio of the mass of hydrogen chloride contained in the hydrochloric acid to the mass of the siloxane small molecules is (2.5×10 -5 ~6.0×10 -3 ): 1; and / or, The mass ratio of the hexamethylenetetramine to the siloxane small molecule is (0.01-0.5):

1.

2. The silica sol according to claim 1, characterized in that The mass ratio of the hexadecyltrimethylammonium bromide to the siloxane small molecule is (2.12×10 -3 ~2.0×10 -1 ): 1; and / or, The mass ratio of the deionized water to the siloxane small molecule is (2.9-4.0):1; and / or, The ratio of the mass of hydrogen chloride contained in the hydrochloric acid to the mass of the siloxane small molecules is (2.5×10 -5 ~3.2×10 -3 ): 1; and / or, The mass ratio of the hexamethylenetetramine to the siloxane small molecule is (0.02-0.5):

1.

3. The silica sol according to claim 1 or 2, characterized in that: The siloxane small molecule is selected from one or more of tetramethyl orthosilicate, tetraethyl orthosilicate, methyltriethoxysilane, methyltrimethoxysilane, ethyltriethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, phenyltriethoxysilane, phenyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, octadecyltrimethoxysilane, and octadecyltriethoxysilane.

4. A method for preparing the silica sol according to any one of claims 1 to 3, characterized in that: Includes steps: Small siloxane molecules, deionized water and hydrochloric acid are mixed and stirred for reaction; then hexadecyltrimethylammonium bromide is introduced and stirred; and then hexamethylenetetramine is introduced and stirred to form a homogeneous solution to obtain the silica sol.

5. A silicon-based aerogel composite material, characterized in that: The method is prepared by using the silica sol according to any one of claims 1 to 3, comprising the steps of: S1. Using the RTM process, first lay a ceramic fiber preform in the mold cavity of the RTM metal mold and evacuate it; S2. Maintaining the vacuum degree of the RTM metal mold at -0.090 MPa to -0.095 MPa, maintaining the negative pressure for 0.5 h to 1.5 h, introducing silica sol into the mold cavity of the RTM metal mold, allowing the silica sol to impregnate the ceramic fiber preform, and then pressurizing to 0.2 MPa to 0.4 MPa, maintaining the pressure for 1 to 4 h, and completing the impregnation process; S3. The RTM metal mold impregnated with S2 is heated and cured, and then demolded to obtain a flat member; S4. The flat plate component is heated to remove water to obtain a silicon-based aerogel composite material.

6. The silicon-based aerogel composite material according to claim 5, characterized in that: The fiber used in the ceramic fiber preform is selected from quartz fiber, mullite fiber, alumina fiber, and zirconia fiber; the apparent density of the ceramic fiber preform is 0.05 g / cm 3 ~0.15g / cm 3 .

7. The silicon-based aerogel composite material according to claim 5, characterized in that: The heating and curing process in step S3 includes: curing by heating in an oven, the heating temperature is 70° C. to 100° C., and the heating time is 10 h to 40 h.

8. The silicon-based aerogel composite material according to claim 5, characterized in that: The heating and dehydration process in step S4 includes: heating at 60° C. to 80° C. for 8 h to 10 h, and then heating to 100° C. to 120° C. for 3 h to 6 h.